Konflik Kawasan: Studi kasus Sengketa Masjidil Al Aqsa - Fudia, Sintaya Luchma; Fajrin, Ahmad Afifudin; Rizqi, Akrima Bunga Yunia; Chasanah, Aisyah Uswatun (Center for Integrative International Studies Laboratory, Faculty of Political and Social Sciences, UIN Sunan Ampel Surabaya, 2022)
Conflict is inseparable in human life. Where there is interaction where it is prone to conflict. conflicts almost occur in all parts of the world, including in the Middle East Region. This conflict in the Middle East began since the fall of the Ottoman Empire during the first world war. as we know the Otoman kingdom has been in power for centuries and has a vast area including the Middle East. the collapse of the Ottoman Empire's power made its territory fall to Great Britain including the Middle East. this is what ultimately gave birth to the